The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jqsrt.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of biological and other organic-carbon aerosol particles in atmosphere using fluorescence

Abstract: a b s t r a c tThis paper offers a brief review on the detection and characterization of biological and other organic-carbon (OC) aerosol particles in atmosphere using laser-induced-fluorescence (LIF) signatures. It focuses on single individual particles or aggregates in the micron and supermicron size range when they are successively drawn through the interrogation volume of a point detection system. Related technologies for these systems that have been developed in last two decades are also discussed. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 104 publications
(241 reference statements)
3
65
0
3
Order By: Relevance
“…Previously it has been reported that real-time LIF analysis enables classification of bioaerosols from other aerosols in atmosphere (Gabey et al 2010;Huffman et al 2010;Pan 2015). Our results show that combined LIF and LIBS analysis is promising tool for online classification of atmospheric bioaerosols.…”
Section: Identification Of Microbial Particlessupporting
confidence: 54%
See 1 more Smart Citation
“…Previously it has been reported that real-time LIF analysis enables classification of bioaerosols from other aerosols in atmosphere (Gabey et al 2010;Huffman et al 2010;Pan 2015). Our results show that combined LIF and LIBS analysis is promising tool for online classification of atmospheric bioaerosols.…”
Section: Identification Of Microbial Particlessupporting
confidence: 54%
“…Fluorescence spectra or fluorescence band (single or multiple) intensity measurement can be utilized to discriminate bioaerosols from other aerosols (P€ ohlker et al 2012;Pan 2015). Fluorescence-based online bioaerosol instruments, such as BioScout, WIBS, and UV-APS, have been used in various environments, but it is really challenging to classify different types of bioaerosols with these instruments (Gabey et al 2010;Huffman et al 2010;Saari et al 2014).…”
Section: Lif Spectra Of Microbial Particlesmentioning
confidence: 99%
“…Для быстрого обнаружения и идентификации патогенных биологических частиц респирабельной (задерживаемой в органах дыхания человека) фракции 1-10 мкм может быть применен проточно-оптический метод (ПОМ) анализа, использующий измерения флюоресценции и рассеяния света от от-дельных частиц аэрозоля [6][7][8]. В ПОМ отбор пробы и освещение частиц происходит в потоке воздуха, что позволяет анализировать до 10 4 отдельных частиц аэрозоля в секунду и выдавать результат анализа за время, не превышающее нескольких минут.…”
unclassified
“…Задача осложняется тем, что био-аэрозольный фон атмосферы -динамичная система, флуоресцентные свойства которой могут меняться в естественных условиях при воздействии солнечного света, температуры, влажности и других факторов [8]. Таким образом, задача правильной идентификации патогенных частиц в составе аэрозоля с помощью ПОМ требует повышения селективности метода.…”
unclassified
See 1 more Smart Citation